Fatores associados à qualidade de vida em pacientes com psoríase: um estudo transversal - Pollo, Camila Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Identificar os fatores associados à qualidade de vida de pacientes com psoríase. Métodos: Estudo transversal, realizado em hospital público do estado de São Paulo, com 300 pacientes com psoríase, utilizando dados sociodemográficos, Escala Hospitalar de Ansiedade e Depressão, Dermatology Life Quality Index, Psoriasis Area and Severity Index e Escala de Estratégias de Enfrentamento. Resultados: Predominaram mulheres 158 (53%), com idade média de 51,9 anos, renda familiar < 3 salários mínimos 173 (72%) e ensino fundamental 162 (54%). O impacto na qualidade de vida foi moderado ou mais 121 (40%). Ensino fundamental (p=0,04), gravidade (p=0,00), COPE-Breve (p=0,02), Depressão (p=0,00), Ansiedade (p=0,01), prurido (p=0,00) influenciaram de forma independente os escores de qualidade de vida. Conclusão: A qualidade de vida dos participantes foi moderadamente afetada ou mais pela psoríase. Baixo nível de escolaridade, utilização de estratégias de enfrentamento, quadro clínico pior, sintomas de ansiedade e depressão contribuíram para pior percepção do constructo.

To identify factors associated with the quality of life of patients with psoriasis. Methods: Cross-sectional study, conducted in a public hospital in the state of São Paulo, with 300 patients with psoriasis, using sociodemographic data, Hospital Anxiety and Depression Scale, Dermatology Life Quality Index, Psoriasis Area and Severity Index and Coping Strategies Scale. Results: 158 (53%) women predominated, with an average age of 51.9 years, family income <3 minimum wages 173 (72%) and elementary school 162 (54%). The impact on quality of life was moderate or more 121 (40%). Elementary education (p = 0.04), severity (p = 0.00), COPE-Brief (p = 0.02), Depression (p = 0.00), Anxiety (p = 0.01), itching (p = 0.00) independently influenced quality of life scores. Conclusion: The quality of life of the participants was moderately affected or more by psoriasis. Low level of education, use of coping strategies, worse clinical picture, symptoms of anxiety and depression contributed to a worse perception of the construct.
Factors associated with quality of life in psoriasis patients: a cross-sectional study
Keywords: Qualidade de vida; Dermatologia; Psoríase; Enfermagem; Pacientes; Quality of life; Dermatology; Psoriasis; Nursing; Patient